THE WONDERS OF MOBILE PHONE TECHNOLOGY IN TEACHING AND LEARNING ENGLISH - Murugan, Agelyia; Sai, George Teoh Boon (Indonesian EFL Journal, 2017)
Using digital tools such as Mobile phones in learning environment is beneficial as the device which is capable to present learning content and provide a wireless two-ways communication between the educator and learners. A review of researches done in Malaysia shows that studies are still focusing on the readiness of the educators and learners in using mobile learning technology in teaching and learning. This paper advocates the use of mobile phones in teaching and learning English. Theories relating to mobile learning highlight the importance of control, context, and communication elements in mobile learning. These three elements are important in knowledge building and support the positive behavioural change of the learners. Apart from that, mobile phones enable the learners to strengthen their language skills as it promotes an environment that motivates the learners to be explorative. In order to meet the students’ needs, there are many types of mobile phone applications that assist learning such as discussion forum, text-based activities, audio-based learning, and interactive game-based language learning. The paper significantly highlights the importance of mobile phones and mobile phone applications which allow language learners to learn and enrich their language anytime and anywhere because the learning process can happen while on the move. Keywords: mobile learning technology, mobile phone, English language skills